2017
DOI: 10.1021/acs.joc.7b00480
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Oxidative Cyclization of 2-Amino-azaarenes with Lignin Models: Synthesis of 3-Phenoxy Imidazo Heterocycles

Abstract: A catalytic oxidative cyclization of 2-aminopyridines or 2-aminobenzothiazole with 2-phenoxyacetophenones (a kind of lignin platform compound) was developed, efficiently providing valuable 3-phenoxy imidazo[1,2-a]pyridines or 3-phenoxy benzo[d]imidazo[2,1-b]thiazoles. The reaction was realized under oxygen by simply using inexpensive CuI as the catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…291,292 Direct transformation of biomass sugars to azaheterocycles has been investigated with profound results, 293,294 while most studies of upgrading lignin are more focused on its model molecules such as 2-phenoxy acetophenone and aromatic aldehydes via modified approaches based on conventional reactions. 295,296 5. Other N-heterocycles…”
Section: Other Fused N-heterocyclesmentioning
confidence: 99%
“…291,292 Direct transformation of biomass sugars to azaheterocycles has been investigated with profound results, 293,294 while most studies of upgrading lignin are more focused on its model molecules such as 2-phenoxy acetophenone and aromatic aldehydes via modified approaches based on conventional reactions. 295,296 5. Other N-heterocycles…”
Section: Other Fused N-heterocyclesmentioning
confidence: 99%
“…33 In the same year, Zhang et al developed a catalytic oxidative cyclisation of 2-aminobenzothiazole with 2-phenoxyacetophenone under oxygen using a CuI catalyst. 34 Recently, a one-pot GroebkeÀBlackburnÀBienaymé synthetic protocol was employed by Sharada et al and the Gámez-Montañ group to synthesize these privileged heterocycles (Scheme 1). [35][36][37] Although the above methodologies are impressive, the development of an efficient and transition-metal-free approach for the diversity-oriented synthesis of both benzo[d]imidazo [2,1b]thiazoles and novel N-alkylated 2-aminobenzo[d]oxazoles derivatives using a simple methodology remains a challenging yet attractive task.…”
Section: While Benzo[d]oxazolementioning
confidence: 99%
“…Literature survey revealed that in recent years assorted transition-metals catalyzed reactions have been reported as a cornerstone for the synthesis of these fused tricyclic heterocyclic core nuclei. A number of catalytic techniques have been envisaged as utilizing the CuOTfÁC 6 H 6 /Cu(OTf) 2 , [10] NaHCO 3 , [11] Cu(OAc) 2 .H 2 O, [12] FeCl 3 /ZnI 2 , [13] Cu(OAc) 2 /Cs 2 CO 3 , [14] CuI, [15] FeCl 3 , [16] Cs 2 CO 3 , [17] I 2 , [18] and Cu(OTf) 2 [19] for the systematic synthesis of these imidazo fused benzothiazole moieties. Although, it was discerned that these accounted methods abide some drawbacks comprises the use of exorbitant, moisture-sensitive reagents, ample reaction time, fatiguing workup procedures, a nonrecyclable and larger amount of catalyst loadings that leads to the production of an immense amount of environmental waste.…”
Section: Introductionmentioning
confidence: 99%